Effects of heat treatment on the chemical composition, antioxidant activity, and toxicity of agarwood oil - Nurul Aduka Syameera, .; Kaewdaungdee, Sanit; Saiful Nizam, Tajuddin; Tanee, Tawatchai; Sudmoon, Runglawan; Chaveerach, Arunrat; Lee, Shiou Yih (Elsevier Ltd, 2024)
The fragrant compound in agarwood has been a valuable ingredient in perfumery. The agarwood oil that is extracted using hydro-distillation technique undergoes a certain heat treatment to blend well with other compounds. As it is highly prized and proprietary, information on the effects of heat treatment on the agarwood oil is limited, hindering its potential as a bioresource in other pharmaceutical and cosmeceutical applications. In this study, we reveal the effects of heat treatment on agarwood oil, with a special focus on terpene compounds – an important chemical component found in agarwood. We found that agarwood oil was thermally stable at the temperatures of 80 °C, 120 °C, and 180 °C and time points 5 min, 10 min, and 20 min, respectively, without causing major loss in its terpene compounds, including monoterpenes, diterpenes sesquiterpenes, and sesquiterpenoids. Further analysis using the DPPH (2,2-diphenyl-1-picrylhydrazyl) antioxidant assay showed an overall increase in free radical scavenging activity for these heated agarwood oil. Additionally, the heat-treated agarwood oil did not return with any toxic effects on mononuclear blood cells. The findings of this study would be beneficial to the downstream applications of agarwood oil in perfumery and pharmaceutical product development.